An analysis of the functionality of selected websites presenting data on air traffic - Krawczyńska Katarzyna; Karsznia Izabela (Polish Cartographical Review, 2020)
The subject of the article is the assessment and comparison of the functionality of websites presenting flight data and the current location of aircraft on the map. The following websites were assessed: Flightradar24 (flightradar24.com), RadarBox24 (radarbox24.com), Flightaware (flightaware.com) and Plane-finder (planefinder.com). The credibility of the presented data and the range of functions available on the websites were analyzed in detail. A number of functions included in data sets were compared to the examined websites. Additionally, the possibilities of expanding the analyzed websites and extending the scope of their functions were determined. The issue of using data from air traffic data websites for scientific research was also examined.